Classification of lactation curves on French dairy goats - Arnal M.; Robert-Granié C.; Larroque H. (Innovation for sustainability in sheep and goats, 2019)
The objective was to achieve a typology of lactation curves and to analyze the influence of environmental factors on these curves. The data used consists of 2,245,628 monthly test-day records of milk on 213,534 Saanen and Alpine French goats. A principal component analysis (PCA) was performed on milk testday records with R package fdapace. Three principal components were found: one related to the level of milk production, another to the persistency and a third to the shape in middle lactation. The first principal component was mainly explained by herd effect, milk yield estimated breeding value (EBV), parity and region. The second one was mainly explained by month of kidding, breed, age at kidding, dry period length, gestation stage, somatic cell score (SCS) EBV, and parity. The third one was mainly driven by the month of lactation. A classification was used on PCA lactation scores and 5 clusters were found.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)